The Determination and Classification of Low Mass Brown Dwarf Stars Using Metallicity Technique - Karim, Layth; Ezzat, Rami; Abdulhamed, Ahmed (Iraqi Journal of Science, 2023)
Low mass brown dwarf stars in the northern hemisphere were investigated; their population and metallicity have been determined using the spectroscopic technique. The classification of these stars was pointed out as belongs to population I, varies in metallicity range between -0.417 ≤ z ≤ 0.143.